PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TEH MERK GAMBYONG (Studi Kasus di Pondok Gambyong dan Homestay Karanganyar) - Widyaningrum, Vivi Rufitasari; Trisnowati, Juni; Pujiani, Dewi (Universitas Of Surakarta, 2023)
This study aims to determine the effect of product quality (X1), price (X2), and promotion (X3) on purchase decisions (Y) of Gambyong Brand Tea (Case Study in Pondok Gambyong and Homestay Karanganyar) either partially or simultaneously. This research is a quantitative research using 100 respondents as the research sample. The analysis technique used in this research is multiple linear regression analysis, t test (partial), F test (simultaneous), and coefficient of determination test (R2). The results of the t-test for product quality (X1) are 2.193, price (X2) is 4.482, and promotion (X3) is 5.092 where the value is > ttable (1.985). The significance level for each variable is 0.031 (product quality), 0.000 (price), 0.000 (promotion) which means <0.05. And then, in the F test for all independent variabels the calculated F result are 57,322 > Ftable (2,70) with a level of significance 0,000 < 0,05.The results showed that product quality (X1), price (X2), and promotion (X3) had a positive and significant influence on purchase decision (Y) either partially or simultaneously.